Influence of cleansers and irrigation methods on primary and permanent root dentin permeability: a literature review - Fernanda Miori Pascon; Kamila Rosamilia Kantovitz; Regina Maria Puppin-Rontani (Universidade Estadual de Campinas, 2015)
This paper review is key issue to known that the adequate endodontic techniques accomplished on primary and permanent teeth regarding the root dentin permeability. Therefore, it was discussed the efficacy of some cleansers and the influence of two irrigation systems used during endodontic preparation of primary and permanent teeth (manual or ultrasonic activation). The literature was searched for original papers relating cleansers characteristics, cleansers effect of root dentin permeability and the influence of manual irrigation or ultrasonic activation systems regarding primary and permanent endodontic therapy. The articles were selected using Bireme and Medline databases. Manual tracing of references cited in key papers otherwise was not elicited. It can be concluded that regarding cleansers and irrigation systems, there are not enough papers focusing primary teeth to establish patterns of change in the root dentin permeability. However, among the solutions used to treat permanent teeth, all solutions and associations studied increased the root dentin permeability. There was no difference in the root dentin permeability for permanent teeth when compared manual and ultrasonic preparation.